Persepsi Mahasiswa Terhadap Ketersediaan Bahan Bacaan dan Layanan Perpustakaan FKIP Universitas Suryakancana - Daud Pamungkas (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2017)
This article describes how the students' perceptions of reading and service availability from the library of FKIP Universitas Suryakacana. The research was conducted descriptively by using instrument in the form of questionnaire and checklist. The results showed that students respond positively to the collections that are available both in terms of quantity and variety. Available collections are considered to fit the needs of the user. Then, in terms of services such as the length of time of lending, the time of service, and the attitudes and skills of the officers, and the available supporting facilities also get a positive assessment from the pemutaka. However, it does not mean everything is perfect. In other words, both the collection and the services of the library FKIP Universitas Suryakancana still need to continue to clean up and innovate for the comfort and passion of students to learn by reading can be better so that will have an impact on improving the quality of teaching and learning process. Keywords: student, perception, reading material, library service.